The Effect Of Sharia Financial Literacy On The Consumer Behavior Of Generation Z Students With Paylater Users As A Mediation Variable - Nur Aisyah; Sofyan Syamsuddin; Sultan (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The purpose of this study is to determine the Influence of Islamic Financial Literacy on the Consumptive Behavior of Generation Z Students with Paylater Users as a Mediation Variable. This study uses a quantitative method by distributing questionnaires to 78 FEB students of the University of Muhammadiyah Palopo class of 2021 as data collection materials which were analyzed with the help of IBM SPSS statistics version 25. The data analysis used in this study is path analysis, which is a development technique of multiple linear regression. The researcher's findings indicate that financial literacy has a positive effect on consumptive behavior with pay later users as a mediating variable. From the results of this study, it can be concluded that generation Z students who have good Islamic financial literacy tend to be wiser in using pay later and controlling consumptive behavior in their daily lives.